“From the Soviet Information Bureau...”: on Information Confrontation of the USSR and Germany During the Great Patriotic War. 1941-1945 - Malysheva Elena Mikhaylovna; Garazha Nataliya Alekseevna (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2015)
The article gives an overview of information confrontation between the USSR and the Third Reich in 1941-1945 in the struggle for the mass consciousness of the civilian population and combatants, shows opposite axiological priorities and forms of propaganda and counter-propaganda of the opposing sides.